Where do banks value corporate social responsibility more? Evidence on the role of national culture - Cheung, Yan-Leung; Tan, Weiqiang; Wang, Wenming (Journal of Banking & Finance, 2020)
Using a sample of loan facilities from 30 countries around the world, we investigate how national cultures affect the relationship between a firm's corporate social responsibility (CSR) performance and its bank borrowing costs. We find that firms with superior CSR performance are more likely to enjoy lower loan interest spreads in countries that exhibit higher levels of egalitarianism and harmony and/or lower levels of hierarchy and mastery. Further analyses reveal that the impact of national culture on the relationship between CSR performance and loan interest spreads is especially significant for borrowing firms with higher customer awareness, heavier R&D intensity, and more opaque information environment. We find national culture of the bank lender itself play an important role in shaping the relation between CSR performance and loan contracting as well. Overall, our findings highlight the important role of national culture in determining the economic consequences of CSR commitments and provide implications for corporate managers who make decisions about CSR strategies.